2014
DOI: 10.22179/revmacn.17.409
|View full text |Cite
|
Sign up to set email alerts
|

Variability of imposex development and reproductive alterations in the Patagonian gastropod Buccinanops globulosus inhabiting a polluted harbour area

Abstract: Abstract:The aim of this work was to study the reproductive output and imposex parameters of the caenogastropod Buccinanops globulosus inhabiting a harbour area, with high maritime traffic and pollution. The results showed higher imposex incidence for non-gravid females than for gravid females (carrying egg capsules). Among imposex-affected females, mean penis size was significantly larger in non-gravid (3.4 mm) than gravid (1.5 mm) females. In B. globulosus usually a single juvenile hatches per egg capsule, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(31 reference statements)
0
2
0
1
Order By: Relevance
“…The data reported in this study indicates that human consumption of B. globulosus collected from contaminated areas should be of concern due to the finding of carcinogenic compounds in their tissues. Previous studies performed in the same harbor zone, have demonstrated imposex presence in B. globulosus (Bigatti et al, 2009), reproductive alterations (Primost et al, 2015a), oxidative stress (Primost et al, 2015c) and bioaccumulation of heavy metals as Cd and Pb (Primost et al, 2017) making the situation more complex from the point of view of the health of the organisms and their consumers, including the human population. Regarding B[a]P, this had concentrations lower than the limit of detection in gastropods although was present in sediments (Table 1).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The data reported in this study indicates that human consumption of B. globulosus collected from contaminated areas should be of concern due to the finding of carcinogenic compounds in their tissues. Previous studies performed in the same harbor zone, have demonstrated imposex presence in B. globulosus (Bigatti et al, 2009), reproductive alterations (Primost et al, 2015a), oxidative stress (Primost et al, 2015c) and bioaccumulation of heavy metals as Cd and Pb (Primost et al, 2017) making the situation more complex from the point of view of the health of the organisms and their consumers, including the human population. Regarding B[a]P, this had concentrations lower than the limit of detection in gastropods although was present in sediments (Table 1).…”
mentioning
confidence: 96%
“…Moderated levels of TBT and their metabolites (DBT and MBT) have been detected in sediments of the Nuevo gulf (Patagonia) (Bigatti et al, 2009) and in gastropods (Del Brio et al, 2016). The incidence of imposex up to 100%, has been demonstrated in the edible gastropod Buccinanops globulosus inhabiting harbor areas contaminated with TBT, as well as oxidative stress, shell malformations, reproductive alterations and acute toxicity in affected populations (Primost et al, 2015a;Primost et al, 2015b;Primost et al, 2015c;Primost et al, 2016;Averbuj et al, 2017;Márquez et al, 2017). Studies carried out in the Patagonian coastal zone of Argentina, related to organic compounds contamination have reported presence of polyaromatic hydrocarbons (PAHs), TBTs and organochlorines (OCPs and PCBs) (Commendatore et al, 2012;Commendatore et al, 2015).…”
mentioning
confidence: 99%
“…Esto puede sugerir la presencia del Se registra imposex en C. crassilabrum para ambas zonas con altas prevalencias de 98% en Playa Hermosa y 100% en la Playa de Pucusana. En esta última, el tráfico marí-timo, por la presencia de embarcaciones pesqueras, es mayor y con mayor densidad (Primost et al, 2015;Batista et al, 2016), además de no mantener un control sobre las pinturas con OTs. Ambas playas tienen una geografía que disminuye la cinética y el hidrodinamismo de la marea, favoreciendo la sedimentación de OTs.…”
Section: Discussionunclassified